Effect of fillet radii upon the performance of a novel shock absorber for an electrically powered vehicle. (4th August 2014) - Stangl, P.K.; Meguid, S.A.
Increasingly stringent anti–pollution laws in North America and Europe have recently stimulated interest in the development of a new generation of electrically powered vehicles. Typically, a large number of conventional lead–acid batteries are utilized in order to ensure adequate performance as measured by vehicle speed and range. The electric vehicle design in this article uses a conventional General Motors G–Van modified to accommodate the electric drive units. A novel shock absorber utilizing a symmetric stepped circular tube has been designed to provide the battery tray with the necessary compliance, thus delaying the effect of its added mass upon impact and reducing the severity of any collision. This is an extension of previous work (Stangl and Meguid. 1989) which examined the overall design of the absorber and its suitability for an electrically powered vehicle. Here, attention was devoted to examining the effect of varying fillet radii upon the force–displacement characteristics, mode of deformation and applicability to use in this vehicle. Accordingly, extensive finite element analysis was performed on the alternative designs using the explicit analysis code, DYNA3D. The results indicate that decreasing the fillet radii reduces the level of forces required to crush the absorber while maintaining the mode of deformation. In contrast, the use of large fillet radii introduces a new mode of deformation with a corresponding higher level of crush load.